THE INFLUENCE OF FUNDAMENTAL FACTORS ON DIVIDEND POLICIES AND FIRM VALUE (STUDIES AT COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE PERIOD 2008 - 2012) - Brimantyo, Harril; Suhadak, Suhadak; Nuzula, Nila Firdausi (FIA UB, 2014)
The purpose of this research is to study the influence of fundamental factors on dividend policies and firm value. There are 12 companies used as a sample of this research in period 2008-2012. The researchers used Partial Least Square (PLS) to analyze and test the relationship among variables. There are seven indicators used in this study; current ratio, debt ratio, and return on investment as fundamental factors indicators; dividend per share and dividend yield as dividend policies indicators; book value and tobinâ€™s q as firm value indicators. Outer model result shows that debt ratio is not valid to be fundamental factors indicator because debt ratio is not significant. Inner model result shows that there are insignificant effect between fundamental factors and firm value, significant effect between fundamental factors and dividend policies, and significant effect between dividend policies and firm value. This result also supports Bird-In-The-Hand Theory from Gordon and Lintner. Â Keyword:Â Fundamental Factors, Dividend Policies, Firm Value